History dependence in wages and cyclical selection: Evidence from Germany - Anja Bauer; Benjamin Lochner (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institute for Economics, 2017)
Using employer-employee data from Germany, this paper analyzes the relationship between wages and past and contemporaneous labor market conditions. Specifically, we test the implications of implicit contract models (Beaudry and DiNardo, 1991) and an on-the-job search model (Hagedorn and Manovskii, 2013) for the wage formation of different worker types over the business cycle. The results are mixed: On the one hand, the data suggest that wages depend on labor market conditions when a match is formed - as contract theories postulate. On the other hand, past labor market conditions also affect contemporaneous wages through the evolution of match quality over a worker's job history - the main hypothesis of the on-the-job-search model. Using cyclical variation in labor market tightness to control for match quality, as in Hagedorn and Manovskii (2013), we find that previous evidence for the excess wage cyclicality of job changers can be entirely explained by cyclical variation of match quality. Refining the selection model by taking into account occupational mobility within employer-employee matches, we also find no excess wage cyclicality for new hires from unemployment - the key worker type's wage for understanding unemployment fluctuations in matching models.
Keywords: E24; E32; J31; J41; 330; Business Cycle; Wage; Wage Rigidity; Implicit Contracts; Match Quality